Csodálatos-e az ember? Az Antigoné első stasimonja - Mezősi, Miklós (Studia Litteraria, 2015)
Antigone, probably the best-known among Sophocles’ extant plays, not only boasts a distinguished and prestigious standing in the canon of world literature but has also been taught at schools for centuries as “the drama about fraternal love.” Can a “re-interpretation” of an “overdiscussed” work like Antigone be justified? Following Martin Heidegger’s translation and interpretation of the First Stasimon in Antigone in Chapter 3 of his Einführung in die Metaphysik, the present essay risks a positive answer to the question raised above. Offering an analysis of the famous choral ode often referred to as the “Ode on Man”, this paper aims to show that the notorious and prevalent misinterpretation (and mistranslation) of the stasimon’s opening lines (“there are many wonders on earth, but none so wondrous as man”) inevitably slackens the ode’s inherent ties with the dramatic context. As a result, this choral song’s ability to fully function as a poetic text is heavily undermined. Delving into the stasimon, this research paper offers to reconstruct a viable meaning for the crucial word in the ode – the adjective deinos – interpreted by many scholars as “wonderful”, with the aim to restore the stasimon’s intrinsic connection with the play, bringing the choral ode back where it really belongs: to the dramatic context.